LAYANAN INFORMASI OLEH GURU BIMBINGAN DAN KONSELINGMENCEGAH PERILAKU MEMBOLOS KELAS VIII SMPN 03 SUNGAI RAYA - Annisa, Annisa; Astuti, Indri; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe method in this research is descriptive method. Form of research used is study survey. The population in the study amounted to 240 students with a sample of 63 students. Data collection techniques used are direct communication techniques and indirect communication techniques. Data collection tools used in the form of interviews and questionnaires.Based on the results of data analysis showed that information services by teachers guidance and counseling in preventing the behavior of ditching students in the class VIII SMP Negeri 03 Sungai Raya reach 88.08% in either category. These findings can be concluded that the information service by guidance and counseling teachers in preventing the behavior of students ditching in the VIII class of SMP Negeri 03 Sungai Raya has been well implemented.Â Keyword: study survey,preventing the behavior of ditching students